1992
DOI: 10.1023/a:1015867608405
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order to study the influence of hydrogen bonding in the amide backbone of a peptide on permeability across a cell membrane, a series of tetrapeptide analogues was prepared from D-phenylalanine. The amide nitrogens in the parent oligomer were sequentially methylated to give a series containing from one to four methyl groups. The transport of these peptides was examined across confluent monolayers of Caco-2 cells as a model of the intestinal mucosa. The results of these studies showed a substantial increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(65 citation statements)
references
References 13 publications
2
63
0
Order By: Relevance
“…26,27 Recently the potential capacity to form intermolecular hydrogen bonds with water has been reintroduced as a predictor of drug and peptide absorption. 28,29 Interestingly, pindolol, metoprolol, and oxprenolol, which have the same potential hydrogen bond formation capacity, had significantly different permeability coefficients, indicating that the theoretical calculation of hydrogen-bonding capacity is not applicable on the -receptor antagonists. This is probably because this simple method does not consider the three-dimensional shape of the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Recently the potential capacity to form intermolecular hydrogen bonds with water has been reintroduced as a predictor of drug and peptide absorption. 28,29 Interestingly, pindolol, metoprolol, and oxprenolol, which have the same potential hydrogen bond formation capacity, had significantly different permeability coefficients, indicating that the theoretical calculation of hydrogen-bonding capacity is not applicable on the -receptor antagonists. This is probably because this simple method does not consider the three-dimensional shape of the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the importance of HBD in permeability might be the predominant presence of hydrogen bond acceptors in the head group regions of membrane bilayer lipids (11). As a result, the permeability of solutes with significant hydrogen bonding donor tendencies is restricted (41,42). The presence of nRotB in the model indicated that a greater flexibility of a molecule favors buccal permeation.…”
Section: Development Of a Predictive Model For Buccal Permeabilitymentioning
confidence: 99%
“…Samples (100 µL) were then withdrawn carefully from the AP side and replaced with the same volume of fresh surfactant solution. Previous studies with this peptide showed it to be stable in the presence of Caco-2 cells; 19 therefore the amount of radioactive peptide transported was determined in a Beckman LS 6000 IC liquid scintillation counter.…”
Section: Introductionmentioning
confidence: 99%